Young People in Crisis: NEETs and Unemployed in EU Regions - Enrico Marelli; Giovanni Bruno; Marcello Signorelli (European Regional Science Association (ERSA), 2013)
In most European countries, the youth unemployment rate is much higher ? at least double but in some countries also triple ? than the adult unemployment rate. The NEET group (young people ?neither in employment, education or training?) is also particularly large. The 2008-09 financial crisis, the consequent Great Recession, the Eurozone sovereign debt crisis and the ensuing austerity measures have increased both the youth unemployment rate and the NEET rate. Moreover, both occurrences are becoming persistent and the risk of a ?lost generation? (as warned by OECD) is increasingly worrying, also in consideration of the severe economic, social and even political consequences. However, the situation is not uniform within the EU. There are significant differences between countries and even between regions within countries. Purpose of this paper is to assess the impact of the crisis on the youth unemployment rate and the NEET rate of the EU regions. Following a brief review of the literature and some descriptive statistics on the mentioned labour market indices, we present our econometric estimates. We use Eurostat?s data for the period 2000-2011 concerning all the NUTS-1 regions. We focus on the changes in both the youth unemployment rate and the NEET rate from 2000-07 to 2008-11. As control variables, in addition to GDP, we consider institutional variables at a country level (e.g. the EPL index) and structural variables at the regional level (percentage of employment in the main sectors). The econometric method is based on a battery of panel data estimators, suitably designed to accommodate dynamics along with the three-dimensional structure of the problem: countries, regions within countries and time. The contribution of this paper is at least threefold. First of all, most of the existing empirical studies are limited to the investigation of the dynamics of youth unemployment rates and on comparisons across countries, but do not consider the alternative indicator, the NEET rate (which is more significant on several grounds). Second, the investigations on the impact of the recent crisis on the labour market indices have been, so far, very few. Third, most researches are carried out at the national level, while similar studies concerning the regional level are quite rare.
Keywords: 330; youth unemployment; NEET rates; crisis impact; EU regions